Electron beam irradiation enhanced of Hibiscus cannabinus fiber strengthen polylactic acid composites. (15th September 2015) - Bee, Soo-Tueen; Sin, Lee Tin; Ratnam, C.T.; Kavee-Raaz, R.R.D.; Tee, Tiam-Ting; Hui, David; Rahmat, A.R.
Abstract: This paper reported the effects of increasing Hibiscus cannabinus fiber (also known as kenaf fiber) loading level on properties of electron beam irradiated polylactic acid/low density polyethylene (PLA/LDPE). PLA and LDPE were compounded with 5–20 parts per hundred resins (phr) of kenaf respectively to enhance mechanical properties. The compounded kenaf added PLA/LDPE samples were electron beam irradiated from 15 to 60 kGy. The physical properties of kenaf added PLA/LDPE samples were characterized using gel content, X-Ray diffraction and scanning electron microscopy analysis. The results showed that the increasing of irradiation dosages in PLA/LDPE have gradually increased the gel content and tensile strength due to the formation of crosslinking networks in polymer matrix. However, the higher loading level of kenaf and irradiation dosages could decrease the elongation at break of PLA/LDPE samples. This is due to the restriction of polymer chains mobility as resulted by the poor interfacial adhesion between polymer matrix and kenaf particles as well as the formation of crosslinking networks in polymer matrix limits the sliding of polymer chains. Meanwhile, the increasing of kenaf loading level also has gradually increased the crystallinity of PLA/LDPE matrix. It is concluded that the electron beam irradiation dosages and amount of kenaf fiber in PLA/LDPE matrix should be kept at maximum 45 kGy and 15 phr, respectively for better combination to enhance the properties of the composites.